SEASONAL POPULATION DYNAMICS AND MANAGEMENT OF DUSKY COTTON BUG (DCB), OXYCARENUS HYALINIPENNIS COSTA IN COTTON - R. A. Khan; M. Naveed (Journal of Animal and Plant Sciences, 2017)
Studies were conducted to see the seasonal population incidence of Dusky Cotton Bug (DCB), Oxycarenus hyalinipennis Costa at the Nuclear Institute for Agriculture & Biology (NIAB), Faisalabad during June, 2015. Data revealed that the incidence of DCB started in the second week of September and reached to the peak level in the first week of October. The population started to decline till first week of November at the termination of the crop. The DCB population recorded low on non-Bt compared to Bt cotton genotypes. The optimum temperature and humidity for DCB was recorded at 35.5 and 41 %, respectively. Moreover, a field bioassay study showed that the mean DCB population remained at 1.8 per boll on imidacloprid, whereas no DCB was recorded on chlorpyriphos after 96 hrs post treatment.
Keywords: Studies were conducted to see the seasonal population incidence of Dusky Cotton Bug (DCB); Oxycarenus hyalinipennis Costa at the Nuclear Institute for Agriculture & Biology (NIAB); Faisalabad during June; 2015. Data revealed that the incidence of DCB started in the second week of September and reached to the peak level in the first week of October. The population started to decline till first week of November at the termination of the crop. The DCB population recorded low on non-Bt compared to Bt cotton genotypes. The optimum temperature and humidity for DCB was recorded at 35.5 and 41 %; respectively. Moreover; a field bioassay study showed that the mean DCB population remained at 1.8 per boll on imidacloprid; whereas no DCB was recorded on chlorpyriphos after 96 hrs post treatment.